2016
DOI: 10.1177/0162643416650024
|View full text |Cite
|
Sign up to set email alerts
|

Using Data to Individualize a Multicomponent, Technology-Based Self-Monitoring Intervention

Abstract: Technology in schools is abundant as is the call for evidence-based interventions for students who need additional support to be successful. One promising use of technology is for self-monitoring interventions aimed at improving classroom behavior. In this study, two middle school students with disabilities used a multicomponent, self-monitoring app on an iPad during their reading classes. Using a data-based individualization approach, teachers worked with the primary investigator to monitor students' response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 21 publications
1
49
0
Order By: Relevance
“…In sum, the reviewed studies reported a consistent increase of on-task behavior and/or decrease of off-task behaviors when MT was integrated fully or partially into self-monitoring (Bedesem, 2012;Bruhn et al, 2016;Bruhn et al, 2015;Gulchak, 2008;Szwed & Bouck, 2013;Vogelgesang et al, 2016;Wills & Mason, 2014) and video-modeling practices (Blood et al, 2011). The provision of EPs seemed to have advantages over the traditional paper-pencil formats in that they prompted higher levels of active academic responding (Haydon et al, 2012) and on-task behavior (Flower, 2014;Haydon et al, 2012).…”
Section: Effectiveness Of Eps Throughout Levels Of Mt Integrationmentioning
confidence: 93%
See 4 more Smart Citations
“…In sum, the reviewed studies reported a consistent increase of on-task behavior and/or decrease of off-task behaviors when MT was integrated fully or partially into self-monitoring (Bedesem, 2012;Bruhn et al, 2016;Bruhn et al, 2015;Gulchak, 2008;Szwed & Bouck, 2013;Vogelgesang et al, 2016;Wills & Mason, 2014) and video-modeling practices (Blood et al, 2011). The provision of EPs seemed to have advantages over the traditional paper-pencil formats in that they prompted higher levels of active academic responding (Haydon et al, 2012) and on-task behavior (Flower, 2014;Haydon et al, 2012).…”
Section: Effectiveness Of Eps Throughout Levels Of Mt Integrationmentioning
confidence: 93%
“…The provision of EPs seemed to have advantages over the traditional paper-pencil formats in that they prompted higher levels of active academic responding (Haydon et al, 2012) and on-task behavior (Flower, 2014;Haydon et al, 2012). Further, EPs appeared to improve academic engagement for elementary (Blood et al, 2011;Flower, 2014;Gulchak, 2008;Szwed & Bouck, 2013;Vogelgesang et al, 2016), middle (Bedesem, 2012;Bruhn et al, 2016;Bruhn et al, 2015) and high school students with ECD (Haydon et al, 2012;Wills & Mason, 2014).…”
Section: Effectiveness Of Eps Throughout Levels Of Mt Integrationmentioning
confidence: 99%
See 3 more Smart Citations